Pelatihan Pembentukan Tim untuk Meningkatkan Kohesivitas Tim pada Kopertis V Yogyakarta - Bachroni, M. (Faculty of Psychology, Universitas Gadjah Mada, 2011)
Currently, employee cohesiveness is a very important factor in determining achievement of an institution’s work plan. Cohesiveness or team cohesively is one factor that determines theeffectiveness of a team work within an institution. One way to improve team cohesiveness is by training. This quasi-experimental study aimed to determine the role of training in enhancing teambuilding cohesiveness of employees in Kopertis V. Experiment subjects are 50 employees in KOPERTIS V. As treatment, team building training is assumed will increase employeecohesiveness. Measurement of team cohesiveness was performed before and after training. Team cohesiveness scale is measuring instrument which responded to complaints based on therating of the team members. The measured data were analyzed using the statistical analysis inferensial paired samples t test. Measured data were analyzed using inferential statisticalanalysis, paired sample t test.